Prototype for wireless remote control of underwater robotic development - Huthaifa Ahmad Al-Issa; Wesam Fouad Swedan; Duha Ahmad Al-Shyyab; Ruwa Ma’mon Altobosh; Ayeh Okleh Altarabsheh (Institute of Advanced Engineering and Science, 2022)
Human beings have been substituted with robots in the performance of tedious and risky activities that human beings do not like or are incapable of performing due to the size of restrictions or the existence of the world, such as outer space or the ocean's depths. It has evolved into a low-cost, dependable, and inexpensive medium that can be used by both scientific societies and different industries for various surveys, mapping, and other underwater activities. In this study of underwater robotics power, we create an underwater robot that can fly in three dimensions: up-down, left-right, and front-back. The robot's motion is monitored by three motors, which also enable it to perform other tasks. Due to the fact that one-third of the world's population lives within 100 kilometers of the ocean, and that we are so focused on land and atmospheric problems that we ignore the seas, it is important to observe marine life and calculate the temperature and strength of light underwater. This application allows determining the appropriate temperature and intensity for living sea creatures to preserve their lives.